Data management technologies and applications : 7th International Conference, DATA 2018, Porto, Portugal, July 26-28, 2018, revised selected papers /: 7th International Conference, DATA 2018, Porto, Portugal, July 26-28, 2018, revised selected papers. ([2019]) - Unknown
No abstract available